Management of Competitive Personnel Training in Higher Education System - Akram Odilovich Ochilov; Shokhrukh Sattor ugli Safarov (Research Parks Publishers, 2021)
Currently, the higher education system of the Republic of Uzbekistan has reached a new level in the information technology society. The role of competitive highly qualified personnel trained in higher education institutions in the development of the country and the welfare of the people is invaluable. In this regard, the article provides information on scientific proposals for the modernization of the higher education system, their basis and expected results.